Beach Topographic Change Analysis Using Multi-temporal UAV Data. Issue 1 (June 2021) - Chang, K T; Fang, H M; Hsiao, S S; Li, C S
Abstract: A time-serial topographic change was performed using two kinds of surveying methods, including direct measurement and indirect remote sensing technology for beach topography surveillance. Compared with reference topographic data, the root mean square error was 0.169 m. From May, 2018 to March, 2019, multi-temporal beach topographic change results indicated that the distance between baseline and shoreline varied in the range of −24.82∼9.58 meter, and weekly variates are −3.16∼0.45 m. The UAV technique can be efficiently used to detect topographic change information in the coastal area.